Co(II), Ni(II), Cu(II), Zn(II), Cd(II) and Hg(II) Complexes with Multidentate Schiff Bases - Kawakeb A. Aziz (College of Education for Pure Sciences, 2008)
Abstract Complexes of the type [M(L)2.2H2O]X2 (where M=Co(II) or Ni(II), X=Cl- or NO3-), [M(L)2Cl2] (where M=Cu(II),Zn(II) or Hg(II)) and [Cd(L)2](NO3)2 where L= multidentate Schiff bases ligands (resulted from the condensation of 2,3-butandione or benzil with 2-aminothiazole) 2-oxo-3-imino-(N-thiazole-2-yl) butane (atc) and 1-oxo-1,2-diphenyl-2-imino-(N-thiazole-2-yl) ethane (atb), have been prepared and characterized by elemental analysis, spectral (Infrared, and U.V./Visible), magnetic data and conductivity measurements. The ligands have been acted as bidentate with Co(II), Ni(II), Cu(II), Zn(II), Hg(II) and tridentate with Cd (II) ions. The prepared complexes had hexacoordinated with octahedral geometries.